Spatial characteristics of urban heat island in Johor Bahru City, Malaysia - Kubota, Tetsu (2009)
This study investigates the spatial characteristics of urban heat island (UHI) in the city of lohor Bahru, Malaysia. Two field measurements were carried out in March (rainy season) and September (dry season) 2008 in order to analyze the spatial distributions of nocturnal air temperature and humidity in the city. The nocturnal temperature difference between the urban and surrounding areas recorded only 2°C in the rainy day, but it reached a maximum of 4°C in the sunny day. More than one UHI were observed in the city. It was found that relatively large open spaces scattered in between the built-up areas may create low air temperature areas and divide the UHI of the city.